2020
DOI: 10.3390/ani10040647
|View full text |Cite
|
Sign up to set email alerts
|

Determining a Welfare Prioritization for Horses Using a Delphi Method

Abstract: Simple Summary: Horses are used for a wide range of different purposes and may be vulnerable to a large number of different welfare issues, some of which are unique to equines, such as responses to being ridden or trained. Compared to farmed livestock, their welfare has received less attention, but concern for their welfare is increasing. Welfare issues can arise from the environments in which animals are kept, how they are treated by their human caregivers and their health. To determine which of the issues ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 54 publications
1
36
0
Order By: Relevance
“…For some issues, it was undoubtedly diicult for our experts to rank the issues simply because there iares limited scientiic or empirical data available on the extent of the welfare issue. There is always the possibility that very diferent results might ensue, depending on the panel of experts participating, 44 although our study in horses 15 showed good agreement with other studies using diferent types of experts. Additionally, consensus methodologies make assumptions on the quality of the expert panel's decisions.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…For some issues, it was undoubtedly diicult for our experts to rank the issues simply because there iares limited scientiic or empirical data available on the extent of the welfare issue. There is always the possibility that very diferent results might ensue, depending on the panel of experts participating, 44 although our study in horses 15 showed good agreement with other studies using diferent types of experts. Additionally, consensus methodologies make assumptions on the quality of the expert panel's decisions.…”
Section: Discussionsupporting
confidence: 84%
“… †See online supplementary materials for the full list of dog welfare issues. ‡See Rioja-Lang et al 15 for the full list of horse welfare issues and ranking. §See Rioja-Lang et al 12 for the full list of rabbit welfare issues and ranking.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly the case when riders are placed, or have placed themselves, within positions of deferral, subservience, and self-ridicule, since it is difficult from this position to evaluate information clearly and decide upon the best course of action. Horsemen et al [ 63 ] (p. 21) and Rioja-Lang et al [ 64 ] (pp. 10–11) identify caregivers’ misrecognition of equine pain as a key welfare challenge facing British equestrianism at present.…”
Section: Discussionmentioning
confidence: 99%